Inspection and monitoring techniques for bridges and civil structures - Fu, Gongkang (Woodhead Publishing in materials., 2005)
With the current emphasis on infrastructure rehabilitation and renewal, advanced techniques for bridge monitoring and assessment are of great interest to civil engineers and those researchers involved in the testing, inspection, management, planning, design, construction, maintenance and life extension of civil structures. The integration of these techniques can lead towards more realistic predictions of the time dependant performance of bridges and civil structures. The potential penalties for ineffective inspection can be catastrophic. The overall emphasis now is on a life extension approach which requires the effective use of NDE techniques and reliability monitoring. This comprehensive new book discusses those techniques requiring physical measurement for inspection and/or monitoring of structures.